1998
DOI: 10.1038/sj.ijo.0800658
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and high blood pressure: Reporting bias related to gender and age

Abstract: OBJECTIVE: To examine the validity of self-reported information on obesity and high blood pressure (HBP) in relation to gender and age, and to explore the impacts of their misclassi®cation on the association between obesity and HBP. DESIGN: Community based cross-sectional study. SUBJECTS: 1791 adult subjects living in Humboldt, Saskatchewan, Canada. MEASUREMENTS: Objectively measured HBP was positive if systolic blood pressure (BP) was !140 mm Hg, diastolic BP was !90 mm Hg or the subject was currently using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…The reason why the association was not confirmed in obese hypertensives may be explained by the fact that this effect was masked in this group by the influence of high BMI. In other words, the association between Nsi\ RFLP of INSR gene and essential hypertension seems to be diluted by the presence of obesity, since obesity itself is known to be caused by various genetic and Schrader et al, 1996 Present study environmental factors, and strongly associated with insulin resistance and essential hypertension (Chen et al, 1998;Kroke et al, 1998;Wannamethee et al, 1998). Therefore, these results strongly suggest that the A/s/l RFLP of INSR gene is associated with essential hypertension, independently of obesity.…”
Section: Discussionmentioning
confidence: 66%
“…The reason why the association was not confirmed in obese hypertensives may be explained by the fact that this effect was masked in this group by the influence of high BMI. In other words, the association between Nsi\ RFLP of INSR gene and essential hypertension seems to be diluted by the presence of obesity, since obesity itself is known to be caused by various genetic and Schrader et al, 1996 Present study environmental factors, and strongly associated with insulin resistance and essential hypertension (Chen et al, 1998;Kroke et al, 1998;Wannamethee et al, 1998). Therefore, these results strongly suggest that the A/s/l RFLP of INSR gene is associated with essential hypertension, independently of obesity.…”
Section: Discussionmentioning
confidence: 66%
“…Such a reporting bias, however, is small and non-differential to disease outcomes, and has little impact on association estimation. 29 In summary, we found that Canadian women ജ40 years of age of low SES had a higher prevalence of type 2 diabetes, independent of age, area of residence, obesity, and physical inactivity. This relationship was weaker in men and accounted for the confounding factors stated above.…”
Section: Discussionmentioning
confidence: 83%
“…This is the first study demonstrating significant sex-specific difference in the degree of association between obesity and blood pressure status by using statistical analysis. There is a controversy regarding the effect of sex on the association between obesity and hypertension: the association has been shown to be stronger in women than in men by a Canadian group [6], not to be different between men and women by Japanese and Croatian groups [7,8] and to be stronger in men than in women by an Indian group [9]. Using white and black American individual, increased OR for prehypertension associated with obesity has been shown to be higher in women than in men, but this sex difference was small in Hispanic Americans [17].…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, using logistic regression analysis and analysis of AUC, the associations of obesity with prehypertension and hypertension were demonstrated to be significantly stronger in women than in men. Interestingly, the sex difference in the association between obesity and hypertension has been shown to become weaker in older age [6], and this suggests involvement of a sex hormone such as estrogen in the sex difference. In the present study, only young people (20-39 years) were enrolled, because menopausal status possibly confounds the relationship between adiposity and blood pressure.…”
Section: <001mentioning
confidence: 97%
See 1 more Smart Citation